Modern tools for predictive business analytics - Zherlitsyn, D. M.; Жерліцин, Д. М. (Baltija Publishing, 2024)
The increasing need for analytical support in managerial decision-making demands continuous enhancement of predictive analytics tools to process, interpret, and visualize large datasets. These technologies enable tracking trends within the business environment, assessing potential risks, and making more informed decisions. Substantial contributions to identifying these trends have been made in recent years, especially in forecasting approaches within data analysis, machine learning, and neural networks.
Сучасні інструменти прогнозної бізнес-аналітики